Analysis of the Attune tibial tray backside: A comparative retrieval study. Issue 3 (March 2019) - Cerquiglini, A.; Henckel, J.; Hothi, H.; Allen, P.; Lewis, J.; Eskelinen, A.; Skinner, J.; Hirschmann, M. T.; Hart, A. J.
Abstract : Objectives: The Attune total knee arthroplasty (TKA) has been used in over 600 000 patients worldwide. Registry data show good clinical outcome; however, concerns over the cement-tibial interface have been reported. We used retrieval analysis to give further insight into this controversial topic. Methods: We examined 12 titanium (Ti) PFC Sigma implants, eight cobalt-chromium (CoCr) PFC Sigma implants, eight cobalt-chromium PFC Sigma rotating platform (RP) implants, and 11 Attune implants. We used a peer-reviewed digital imaging method to quantify the amount of cement attached to the backside of each tibial tray. We then measured: 1) the size of tibial tray thickness, tray projections, peripheral lips, and undercuts; and 2) surface roughness (Ra) on the backside and keel of the trays. Statistical analyses were performed to investigate differences between the two designs. Results: There was no evidence of cement attachment on any of the 11 Attune trays examined. There were significant differences between Ti and CoCr PFC Sigma implants and Attune designs (p < 0.05); however, there was no significant difference between CoCr PFC Sigma RP and Attune designs (p > 0.05). There were significant differences in the design features between the investigated designs (p < 0.05). Conclusion: The majority of the earliest PFC Sigma designs showed evidence of cement, while all of the retrieved Attune trays and the majority of the RP PFC trays in this study had no cement attached. This may be attributable to the design differences of these implants, in particular in relation to the cement pockets. Our results may help explain a controversial aspect related to cement attachment in a recently introduced TKA design. Cite this article : A. Cerquiglini, J. Henckel, H. Hothi, P. Allen, J. Lewis, A. Eskelinen, J. Skinner, M. T. Hirschmann, A. J. Hart. Analysis of the Attune tibial tray backside: A comparative retrieval study. Bone Joint Res 2019;8:136–145. DOI: 10.1302/2046-3758.83.BJJ-2018-0102.R2.